Sensibilidade da Escala de Equilíbrio de Berg em indivíduos com osteoartrite Sensitivity of the Berg balance scale in patients with osteoarthritis - Ana Carolina da Silva Souza (Motriz: Revista de Educacao Fisica, 2012)
Este estudo teve objetivo de analisar a sensibilidade e especificidade da Escala de Equilíbrio de Berg (EEB) em detectar o risco de queda em indivíduos com osteoartrite de joelho (OAJ). Verificar a associação entre a capacidade funcional, grau de OAJ, quadro álgico, índice de medo de cair e histórico de queda com o escore da EEB. Participaram 69 indivíduos com OAJ. Foram analisados os pontos de corte 45, 47, 49, 51 e 53 pontos da EEB, quanto à sensibilidade e especificidade do teste. Utilizou-se a escala analógica visual e os questionários WOMAC e Índice de preocupação em cair (FES-I). Os resultados evidenciaram diferença significativa (p=0,001) no escore da EEB entre os indivíduos com OAJ com e sem história de queda. A EEB apresentou correlação com Womac, FES-I, histórico de queda e grau de OAJ. A EEB não apresentou um ponto de corte ideal para indivíduos com OAJ. Contudo, a escala é sensível às diferenças individuais nesta população. The study has aim of analyze the sensitivity of the (BBS) to detect the risk of falling in individuals with knee osteoarthritis (KOA), and to investigate an association between functional capacity, KOA degree, pain, index of fear of falling, and history of falls with the BBS score. Method: Participants were 69 individuals with KOA. The BBS 45, 47, 49, 51 and 53 cut-off points were used to analyze sensitivity and specificity of the test. The WOMAC questionnaire, Falls Efficacy Scale International (FES-I) and visual analog scale were herein used. The results showed significant differences between the KOA groups with and without history of falls. The BBS showed a strong correlation between the Womac and the FES-I, and moderate correlation between history of falls and KOA degree. The BBS did not show an ideal cut-off point for individuals with KOA. However, the scale is sensitive to individual differences in this population.